Rasch Analysis of Creative Thinking Skill on Optical Instrument (CTSOI) 11th Grade Students Sundanese Tribe: a Case Study - Ghina Aghnia Nur Assyifaa; Eis Nurzakiyah; Lilik Hasanah; Hera Novia (Universitas Muhammadiyah Purworejo, 2021)
This study aims to determine the creative thinking skills at optic instruments of Sundanese tribe, 11th-grade students. This research is a case study research conducted at a high school in Majalengka district, West Java. Totaling 32 students consisting of 12 male students, namely “Aa”, 20 female students, namely “Teteh”, and 18 Sundanese, the rest are immigrants. The instrument used is the Test for Creative Thinking-optical instrument (TCT-OI) which has existed validated by experts. The data found were investigated with Rasch Analysis Model (RAM). Based on the results of the analysis using the Rasch Analysis, it was found that the creative thinking ability of students stayed static low can be shown by the value of Person reliability which is 0.21 included in the weak category. There are variances in the level of creative thinking skills of students from the Sundanese and non-Sundanese tribes. As a result, it is necessary to develop creative thinking skill on the optical instrument, 11th grade students Sundanese tribe